Positive electrode active material, preparation method thereof and battery
By setting a transition metal phosphate coating on the surface of lithium ferromanganese phosphate material, the problems of low energy density and manganese element dissolution of lithium ferromanganese phosphate material are solved, and higher electrochemical performance and structural stability are achieved.
Patent Information
- Application Number
- CN202411814812.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
There are many problems in the production and application of existing lithium manganese ferroferric phosphate materials, including low energy density and manganese element dissolution, which affect the cycle life of the battery and the discharge platform voltage.
By providing a cladding layer of transition metal phosphate on the surface of the lithium ferromanganese phosphate material, the thickness of the cladding layer is controlled to be in the range of 0 < r/D ≤ 0.2 to reduce the impedance of the material and the dissolution of manganese elements.
It effectively improves the electrochemical performance of the positive electrode active material, enhances structural stability, inhibits the dissolution of manganese elements, improves the stability of the charge and discharge platform voltage, and reduces the powder impedance.
Smart Images

Figure CN119650640A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular, to positive electrode active materials and preparation methods thereof, and batteries. Background Art
[0002] Lithium-ion battery is a new type of battery with high capacity, long life and high platform voltage. In recent years, it has been widely used in the fields of power and energy storage, and plays an important role in electronic information, transportation, energy equipment, national defense construction, etc. The positive electrode active material is a key material in the lithium-ion battery system, which determines the energy density, working voltage, cycle and storage life of the battery. The phosphate-based positive electrode active material, mainly olivine-type lithium iron phosphate, is one of the positive electrode active material systems with mature commercial applications in recent years. Lithium iron phosphate materials have the characteristics of long cycle life and stable discharge platform voltage, but compared with ternary materials (lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, etc.), the gram capacity, compaction density and discharge platform voltage of lithium iron phosphate materials are all low, which results in the low energy density of batteries using lithium iron phosphate materials. The lithium iron phosphate obtained by adding manganese elements to lithium iron phosphate has a higher discharge platform voltage than lithium iron phosphate. Under the condition of similar theoretical capacity, the energy density of the battery using this lithium iron phosphate material is relatively high. However, the current lithium manganese iron phosphate materials still have many problems in the actual production and application process that need to be further improved. Summary of the invention
[0003] In the first aspect of the present application, the present application proposes a positive electrode active material, comprising: a core, the core comprising lithium manganese iron phosphate; a coating layer, the coating layer covering at least a portion of the surface of the core, the coating layer comprising a transition metal phosphate, wherein the particle size of the positive electrode active material is D, the thickness of the coating layer is r, 0<r / D≤0.2. Thus, the impedance of the positive electrode active material can be reduced and the electrochemical performance of the positive electrode active material can be improved.
[0004] In some embodiments, 0.1 μm ≤ r ≤ 5.0 μm, and / or 4 μm ≤ D ≤ 25 μm. Thus, by setting a relatively thin coating layer, the dissolution of manganese in the core can be effectively suppressed, and the particle size of the positive electrode active material is moderate, the diffusion distance of lithium ions in the core is short, and it is easy to form a coating layer with a relatively complete structure on the surface of the core.
[0005] In some embodiments, in the positive electrode active material, the molar ratio of the lithium manganese iron phosphate to the transition metal phosphate is 1:(0.01-0.5). As a result, the coating layer accounts for a small proportion, has a small impact on the gram capacity of the positive electrode active material, and the positive electrode active material has a higher gram capacity.
[0006] In some embodiments, the distribution function k of the positive electrode active material is 0.7-1.3, wherein k=(D 90 -D 50 ) / (D 50 -D 10 ), D 90 D is the particle size corresponding to the cumulative volume particle size of primary particles in the positive electrode active material reaching 90%, 50 D is the particle size corresponding to the cumulative volume particle size of primary particles in the positive electrode active material reaching 50%, 10 The particle size corresponding to the cumulative volume particle size of the primary particles in the positive electrode active material reaches 10%. Therefore, the particle size distribution of the primary particles in the positive electrode active material is relatively concentrated, and the particle size distribution uniformity of the primary particles is relatively high.
[0007] In some embodiments, 200 nm ≤ D 90 ≤250nm, 100nm≤D 50 ≤160nm, 50nm≤D 10 ≤80nm. As a result, the positive electrode active material has a higher structural stability.
[0008] In some embodiments, the lithium manganese iron phosphate satisfies the general formula Li a1 Mn x Fe 1-x M z P b1 O c1 , wherein M includes at least one of Mg, Si, V, Co, Ni, Ga, Zr, Mo, Sn, Nb, In, Ce, and W, 1<a1≤1.2, 0.5≤x≤1, 0≤z≤0.2, 1≤b1≤1.2, and 4≤c1≤4.2. As a result, lithium manganese iron phosphate has a better discharge platform voltage and structural stability.
[0009] In some embodiments, the transition metal phosphate satisfies the general formula Li a2 Me y P b2 O c2 , wherein Me includes at least one of Cr, V, Ni, Co, Nb, Mo, Zr, Hf, W, Y, La, and Ce, 1<a2≤1.1, 1≤y≤1.1, 1≤b2≤1.1, and 4≤c2≤4.2. Thus, the transition metal phosphate can effectively reduce the impedance of the positive electrode active material.
[0010] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned positive electrode active material, comprising: mixing a first lithium source, a manganese source, an iron source, and a first phosphorus source to obtain a first mixture; performing a first sintering treatment on the first mixture to obtain lithium manganese iron phosphate; mixing the lithium manganese iron phosphate, a second lithium source, a second phosphorus source, and a Me source to obtain a second mixture, wherein the molar ratio of the lithium manganese iron phosphate to the Me source is 1:(0.01-0.2); performing a second sintering treatment on the second mixture to obtain a transition metal phosphate formed on the surface of the lithium manganese iron phosphate to obtain the positive electrode active material. Thus, the aforementioned positive electrode active material can be obtained by a relatively simple method.
[0011] In some embodiments, the first lithium source and the second lithium source independently include at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate, and lithium chloride; and / or, the first phosphorus source and the second phosphorus source independently include at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and sodium dihydrogen phosphate; and / or, the manganese source includes at least one of manganese tetraoxide, manganese dioxide, manganese carbonate, manganese oxalate, manganese chloride, manganese sulfate, and manganese nitrate; and / or, the iron source includes at least one of ferrous oxalate, ferrous oxalate, ferrous acetate, ferrous acetate, ferrous nitrate, ferric nitrate, ferric phosphate, ferric oxide, ferrous sulfate, ferrous sulfate, ferrous chloride, and ferric chloride; and / or, the Me source includes at least one of metal oxides, hydroxides, phosphides, acetates, and oxalates corresponding to the Me element. As a result, raw materials are easy to obtain, the process route is simple and clear, and it can be quickly introduced and applied based on existing mature processes and equipment.
[0012] In some embodiments, the first mixture further includes a carbon source, and the carbon source includes at least one of citric acid, glucose, sucrose, soluble starch, salicylic acid, tartaric acid, oxalic acid, polyethylene glycol, and polyaniline. Thus, the conductivity of the prepared positive electrode active material can be effectively improved by adding the carbon source.
[0013] In some embodiments, the molar ratio of the first lithium source, the manganese source, the iron source, the first phosphorus source, and the carbon source is (1-1.5):(0-1):(0-1):(1-1.5):(0-0.1). Thus, the conductivity of the positive electrode active material can be effectively improved by adding a small amount of carbon source.
[0014] In some embodiments, the temperature of the first sintering treatment is 350°C-650°C, and the time of the first sintering treatment is 2h-10h; and / or, the temperature of the second sintering treatment is 550°C-850°C, and the time of the second sintering treatment is 6h-16h. Thus, the two sintering treatments can promote the full combination of transition metal phosphate and lithium manganese iron phosphate while maintaining the stability of the core structure.
[0015] In the third aspect of the present application, the present application proposes a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the aforementioned positive electrode active material, or the positive electrode active material prepared by the aforementioned method. Thus, the battery has a higher discharge platform voltage and a better cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0017] Figure 1 This is a scanning electron microscope-energy dispersive spectrometer image of the positive electrode active material of one embodiment of the present application.
[0018] Figure 2 This is a cumulative volume particle size distribution diagram of primary particles of a positive electrode active material according to one embodiment of the present application.
[0019] Figure 3 The charge and discharge curves of the material in Example 1 before and after 80 cycles.
[0020] Figure 4 This is the charge and discharge curve of the material in comparative example 1 before and after 80 cycles.
[0021] Figure 5 This is the charge and discharge curve of the material in Example 2 before and after 80 cycles. DETAILED DESCRIPTION
[0022] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0023] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0024] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0025] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0026] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0027] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0028] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0029] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0031] The longitudinal Mn-O bonds in the lattice of lithium manganese iron phosphate materials are easy to stretch, and the horizontal Mn-O bonds are easy to shorten, which can easily cause Jahn-Teller distortion in the lattice. Jahn-Teller distortion will cause irreversible phase changes in lithium manganese iron phosphate materials, accelerate the destruction and inactivation of the material structure, and cause the manganese element in the lithium manganese iron phosphate material to dissolve, resulting in the attenuation of the platform voltage of the battery during the charging and discharging process. At the same time, the electronic conductivity of lithium manganese iron phosphate materials is low, and their own impedance is large, which will also affect the discharge platform voltage and cycle life of the battery. In response to the problems of manganese element dissolution and high impedance in lithium manganese iron phosphate materials, although the improvement methods in related technologies can improve performance to a certain extent, the lithium manganese iron phosphate materials used have a complex structure and a relatively cumbersome process route, which is not conducive to the large-scale mass production and application of materials and products.
[0032] As an example, the Jahn-Teller effect refers to the phenomenon that in nonlinear molecules, electrons asymmetrically occupy degenerate molecular orbitals, causing the geometric configuration of the molecule to be distorted, thereby eliminating the energy level degeneracy.
[0033] In the present application, by setting a coating layer of transition metal phosphate on the surface of the lithium manganese iron phosphate material, the transition metal phosphate coating layer has little effect on the deintercalation of lithium ions in the core, and can provide electron channels and structural protection. The coating layer is tightly combined with the core, improving the uniformity of the particle size of the primary particles in the core, thereby effectively improving the structural stability of the positive electrode active material, inhibiting the dissolution of manganese elements in the positive electrode active material during the charge and discharge process, improving the stability of the charge and discharge platform voltage, and at the same time reducing the powder impedance of the positive electrode active material, and comprehensively improving the electrochemical performance of the positive electrode active material.
[0034] In the first aspect of the present application, the present application proposes a positive electrode active material, comprising: a core, the core comprising lithium manganese iron phosphate; a coating layer, the coating layer covering at least a portion of the surface of the core, the coating layer comprising a transition metal phosphate, wherein the particle size of the positive electrode active material is D, the thickness of the coating layer is r, 0<r / D≤0.2. Thus, the impedance of the positive electrode active material can be reduced and the electrochemical performance of the positive electrode active material can be improved.
[0035] As an example, refer to Figure 1The particle size of the positive electrode active material and the thickness of the coating layer can be obtained by scanning electron microscope section combined with energy spectrometer test. For example, any diameter in the cross-sectional view of the positive electrode active material can be sampled and tested. Among them, the thickness r of the coating layer is the width of the corresponding area when the energy spectrum intensity of the characteristic elements in the transition metal phosphate is greater than or equal to 80% in the cross-sectional line scanning mode of the positive electrode active material, and the particle size D of the positive electrode active material is the cross-sectional diameter of the corresponding particle. Specifically, the equipment used can be Oxford Instruments Ultim Max 170mm 2 The energy spectrum detector is used to cut the sample into sections, and the SEM scanning mode is adjusted to perform line scanning in the diameter direction. The energy spectrum detector receives characteristic X-rays of different elements, analyzes the selected line segment, and statistically presents the signal intensity change trend line of the specific element on the line segment. The diameter of the single sampling secondary ball scanning is D, and the length of the signal range of the specific element collected on one side is defined as r.
[0036] In some embodiments, the inner core is a secondary particle with a larger particle size formed by agglomeration of lithium manganese iron phosphate primary particles, and the particle size D of the positive electrode active material is the sum of twice the coating layer thickness r and the particle size of the inner core secondary particle.
[0037] It should be noted that, because the particle sizes of different positive electrode active materials are different, the corresponding coating thicknesses are also different. For example, for positive electrode active material particles with larger particle sizes, the coating thickness will be larger; for positive electrode active material particles with smaller particle sizes, the absolute value of the coating thickness will be smaller. The aforementioned r / D means that for the same particle, the particle size D of the positive electrode active material and the thickness r of the coating are tested separately, and the r / D value of the particle meets the aforementioned requirements, but not that the ratio of the coating thickness r of any positive electrode active material particle to the particle size D of another positive electrode active material particle meets the aforementioned limitations.
[0038] In some embodiments, 0.1 μm≤r≤5.0 μm.
[0039] As an example, the thickness r of the coating layer may be 0.1 μm, 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm.
[0040] The transition metal phosphate in the coating layer can provide an electron channel and can improve the conductivity of the positive electrode active material. When the thickness of the coating layer is within the aforementioned range, by setting a thinner coating layer, the dissolution of manganese in the core can be effectively suppressed, and the effect on the deintercalation of lithium ions in the core is small, and the powder impedance of the positive electrode active material can also be reduced.
[0041] In some embodiments, 4 μm ≤ D ≤ 25 μm.
[0042] As an example, the particle size D of the positive electrode active material may be 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, or 25 μm.
[0043] When the particle size of the positive electrode active material is within the aforementioned range, the diffusion distance of lithium ions in the inner core is shorter, and a coating layer with a relatively complete structure is easily formed on the surface of the inner core.
[0044] In some embodiments, in the positive electrode active material, the molar ratio of the lithium manganese iron phosphate to the transition metal phosphate is 1:(0.01-0.5). As a result, the coating layer accounts for a small proportion, has a small impact on the gram capacity of the positive electrode active material, and the positive electrode active material has a higher gram capacity.
[0045] As an example, the molar ratio of lithium manganese iron phosphate to transition metal phosphate may be 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, or 1:0.5.
[0046] When the molar ratio of lithium manganese iron phosphate to transition metal phosphate is within the aforementioned range, the coating layer can achieve a better coating effect on the core and has little effect on the electrical properties of the core.
[0047] In some embodiments, the distribution function k of the positive electrode active material is 0.7-1.3, wherein k=(D 90 -D 50 ) / (D 50 -D 10 ), D 90 D is the particle size corresponding to the cumulative volume particle size of primary particles in the positive electrode active material reaching 90%, 50 D is the particle size corresponding to the cumulative volume particle size of primary particles in the positive electrode active material reaching 50%, 10 The particle size corresponding to the cumulative volume particle size of the primary particles in the positive electrode active material reaches 10%. Therefore, the particle size distribution of the primary particles in the positive electrode active material is relatively concentrated, and the particle size distribution uniformity of the primary particles is relatively high.
[0048] As an example, k may be 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or 1.3.
[0049] When the distribution function k is within the aforementioned range, it indicates that the particle size distribution uniformity of the primary particles (grains) in the positive electrode active material is higher, the primary particles are more densely packed, and more active substances can be accommodated in a limited space, thereby increasing the volume energy density of the battery. In addition, a higher uniformity in particle size distribution can reduce the stress difference between primary particles, reduce the pulverization and shedding of electrode materials caused by inconsistent particle volume changes during the charge and discharge cycle, and improve the cycle performance of the battery.
[0050] As an example, the distribution function k of the positive electrode active material can be measured by powder X-ray diffraction (XRD). Specifically, the crystallite diameter distribution function curve is obtained with the volume-based crystallite diameter as the horizontal axis and the probability density function of the crystallite relative to the crystallite diameter as the vertical axis, so as to calculate the particle size distribution of the primary particles in the positive electrode active material.
[0051] As an example, the particle size distribution of primary particles in the positive electrode active material can be tested by the following method: using XRD Smartlab 9KW, scanning range 10°-80°, voltage 40kV, current 200mA, step 0.02°, scanning speed 2° / min. The test results are obtained by using the WPPF grain size distribution function of SmartLab Studio II software according to the Fundamental Parameter method (FP method) to perform statistical calculations on the crystallite size.
[0052] In some embodiments, 200 nm ≤ D 90 ≤250nm, 100nm≤D 50 ≤160nm, 50nm≤D 10 ≤80nm. As a result, the positive electrode active material has a higher structural stability.
[0053] As an example, D 90 It can be 200nm, 210nm, 220nm, 230nm, 240nm or 250nm.
[0054] As an example, D 50 It may be 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm or 160 nm.
[0055] As an example, D 10 It can be 50nm, 60nm, 70nm or 80nm.
[0056] When D 90 , D 50 , D 10When they are within the aforementioned ranges, the numerical ranges of the three are relatively close, indicating that the particle size distribution of the primary particles in the positive electrode active material is relatively uniform.
[0057] As an example, refer to Figure 2 , D of primary particles in the positive electrode active material 90 215nm, D 50 152nm, D 10 It is 73nm, and calculation shows that k=0.80.
[0058] In some embodiments, the lithium manganese iron phosphate satisfies the general formula Li a1 Mn x Fe 1-x M z P b1 O c1 , wherein M includes at least one of Mg, Si, V, Co, Ni, Ga, Zr, Mo, Sn, Nb, In, Ce, and W, 1<a1≤1.2, 0.5≤x≤1, 0≤z≤0.2, 1≤b1≤1.2, and 4≤c1≤4.2. As a result, lithium manganese iron phosphate has a better discharge platform voltage and structural stability.
[0059] In some embodiments, the transition metal phosphate satisfies the general formula Li a2 Me y P b2 O c2 , wherein Me includes at least one of Cr, V, Ni, Co, Nb, Mo, Zr, Hf, W, Y, La, and Ce, 1<a2≤1.1, 1≤y≤1.1, 1≤b2≤1.1, and 4≤c2≤4.2. Thus, the transition metal phosphate can provide an electron channel, thereby effectively reducing the impedance of the positive electrode active material.
[0060] In some embodiments, Me includes at least one of Ni, Co, Nb, and W.
[0061] Lithium nickel phosphate and lithium cobalt phosphate can improve the high-voltage resistance of the positive electrode active material, and lithium cobalt phosphate can also improve the surface conductivity of the positive electrode active material; lithium niobium phosphate and lithium tungsten phosphate have the function of refining the primary particles and can improve the distribution uniformity of the primary particles in the positive electrode active material.
[0062] In some embodiments, an appropriate amount of carbon source may be added during the preparation of the positive electrode active material. For example, a carbon source may be added during the preparation of the inner core, thereby facilitating the formation of a conductive network in the positive electrode active material and improving the conductivity of the positive electrode active material.
[0063] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned positive electrode active material, by introducing different lithium sources, manganese sources, iron sources, and phosphorus sources as raw materials, mixing them in proportion and performing a first sintering treatment to form a lithium manganese iron phosphate core; then the lithium manganese iron phosphate is mixed with the added lithium salt, phosphorus salt, and raw materials containing the Me element, and after a second sintering treatment, a transition metal phosphate coating is formed on the outside of the lithium manganese iron phosphate. Among them, the added second lithium source and the second phosphorus source can enter the core through the second sintering treatment, balance the distribution of lithium and phosphorus in different regions of the core, make the growth of primary particles in the core more uniform, and form uniformly grown transition metal phosphates on the surface of the core, reduce the local enrichment growth of primary particles, thereby achieving uniform distribution of primary particles in the core and the coating layer and full combination of the coating layer and the core. The aforementioned method for preparing positive electrode active materials has a simple process path, can use existing mature equipment production lines, and is suitable for large-scale industrial production. Specifically, it includes the following steps:
[0064] S1: Mixing a first lithium source, a manganese source, an iron source, and a first phosphorus source to obtain a first mixture
[0065] In some embodiments, in this step, a first lithium source, a manganese source, an iron source, and a first phosphorus source are added to deionized water according to the molar ratio of the target product, and are fully mixed to form a slurry. The slurry is then transferred to a sand mill containing zirconium dioxide grinding balls, ground for a certain period of time, and then spray-dried to obtain a first mixture.
[0066] In some embodiments, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate, and lithium chloride.
[0067] In some embodiments, the first phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and sodium dihydrogen phosphate.
[0068] In some embodiments, the manganese source includes at least one of manganese tetraoxide, manganese dioxide, manganese carbonate, manganese oxalate, manganese chloride, manganese sulfate, and manganese nitrate.
[0069] In some embodiments, the iron source includes at least one of ferrous oxalate, ferrous oxalate, ferrous acetate, ferrous acetate, ferrous nitrate, ferric nitrate, ferric phosphate, ferric oxide, ferrous sulfate, ferric sulfate, ferrous chloride, and ferric chloride.
[0070] In some embodiments, the first mixture further includes a carbon source, and the carbon source includes at least one of citric acid, glucose, sucrose, soluble starch, salicylic acid, tartaric acid, oxalic acid, polyethylene glycol, and polyaniline. Thus, by adding the carbon source, a carbon material composite lithium manganese iron phosphate can be obtained after the first sintering treatment, effectively improving the conductivity of the prepared positive electrode active material.
[0071] As an example, a carbon source may be added to the first precursor slurry.
[0072] In some embodiments, the molar ratio of the first lithium source, the manganese source, the iron source, the first phosphorus source, and the carbon source is (1-1.5):(0-1):(0-1):(1-1.5):(0-0.1). Thus, the addition of sufficient lithium source and phosphorus source helps the manganese source and the iron source to fully react, reduce costs, and reduce waste; the addition of a small amount of carbon source can effectively improve the conductivity of the positive electrode active material, and obtain a carbon material composite lithium manganese iron phosphate.
[0073] S2: performing a first sintering process on the first mixture to obtain lithium manganese iron phosphate
[0074] In some embodiments, the first mixture is subjected to a first sintering process in a reducing atmosphere to obtain lithium manganese iron phosphate.
[0075] In some embodiments, the temperature of the first sintering treatment is 350° C.-650° C., and the time of the first sintering treatment is 2 h-10 h.
[0076] As an example, the temperature of the first sintering process may be 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C.
[0077] As an example, the time of the first sintering process may be 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0078] When the temperature and time of the first sintering treatment are within the aforementioned range, lithium manganese iron phosphate primary particles are initially formed, and the primary particles have a smaller particle size and higher uniformity, which helps to further control the particle size uniformity of the primary particles through the second sintering treatment.
[0079] S3: Mixing the lithium manganese iron phosphate, the second lithium source, the second phosphorus source, and the Me source to obtain a second mixture
[0080] In some embodiments, in this step, the lithium manganese iron phosphate is fully stirred and mixed with a slightly excess second lithium source, a slightly excess second phosphorus source, a Me source and a dispersant, and then filtered and dried to obtain a second mixture.
[0081] In some embodiments, in this step, the lithium manganese iron phosphate is fully stirred and mixed with a slightly excess second lithium source, a slightly excess second phosphorus source, a Me source and a dispersant, and then spray-dried to obtain a second mixture.
[0082] In some embodiments, when the second lithium source contains phosphorus, the second phosphorus source may not be added. Similarly, when the second phosphorus source contains lithium, the second lithium source may not be added. For example, when lithium dihydrogen phosphate (LiH2PO4) is used as the second phosphorus source, the second lithium source may not be added.
[0083] In some embodiments, the molar ratio of the lithium manganese iron phosphate to the Me source is 1:(0.01-0.2).
[0084] As an example, the molar ratio of lithium manganese iron phosphate to Me source can be 1:0.01, 1:0.05, 1:0.1, 1:0.15, or 1:0.2.
[0085] By adding a small amount of Me source, a transition metal phosphate coating layer can be formed by a second sintering treatment, and the molar ratio of the lithium manganese iron phosphate to the transition metal phosphate in the prepared positive electrode active material can satisfy 1: (0.01-0.5), that is, by adjusting the molar ratio of the lithium manganese iron phosphate to the Me source, the molar ratio of the lithium manganese iron phosphate to the transition metal phosphate in the positive electrode active material can be adjusted. For example, when each mole of Me source contains 1 mole of Me element, the molar ratio of the lithium manganese iron phosphate to the Me source is equal to the molar ratio of the lithium manganese iron phosphate to the transition metal phosphate in the positive electrode active material. When each mole of Me source contains 2 moles of Me element, the molar ratio of the lithium manganese iron phosphate to the Me source is equal to twice the molar ratio of the lithium manganese iron phosphate to the transition metal phosphate in the positive electrode active material, and so on.
[0086] In some embodiments, the dispersant includes at least one of polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone.
[0087] In some embodiments, the second lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate, and lithium chloride.
[0088] As an example, the second lithium source and the first lithium source may be made of the same material.
[0089] In some embodiments, the second phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and sodium dihydrogen phosphate.
[0090] As an example, the second phosphorus source and the first phosphorus source may be the same material.
[0091] In some embodiments, the Me source includes at least one of metal oxides, hydroxides, phosphides, acetates, and oxalates corresponding to the Me element. As a result, the raw materials are easy to obtain, the process route is simple and clear, and it can be quickly introduced and applied based on existing mature processes and equipment. Specifically, Me includes at least one of Cr, V, Ni, Co, Nb, Mo, Zr, Hf, W, Y, La, and Ce.
[0092] S4: performing a second sintering treatment on the second mixture to form a transition metal phosphate on the surface of the lithium manganese iron phosphate to obtain the positive electrode active material
[0093] In some embodiments, at this step, the second mixture is subjected to a second sintering treatment in a reducing atmosphere.
[0094] In some embodiments, the temperature of the second sintering treatment is 550° C.-850° C., and the time of the second sintering treatment is 6 hours-16 hours. Thus, the two sintering treatments can promote the full combination of transition metal phosphate and lithium manganese iron phosphate while maintaining the stability of the core structure.
[0095] As an example, the temperature of the second sintering process may be 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, or 850°C.
[0096] As an example, the time of the second sintering process may be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or 16 h.
[0097] When the temperature and time of the second sintering treatment are within the aforementioned range, the added second lithium source and second phosphorus source can enter the inner core, balance the distribution of lithium and phosphorus in different regions of the inner core, and enable the primary particles in the inner core to undergo more uniform secondary growth. At the same time, uniformly grown transition metal phosphates can be formed on the surface of the inner core.
[0098] In the third aspect of the present application, the present application proposes a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the aforementioned positive electrode active material, or the positive electrode active material prepared by the aforementioned method. Thus, the battery has a higher discharge platform voltage and a better cycle life.
[0099] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0100] Example 1
[0101] Li2CO3, Mn3O4, Fe2O3, NH4H2PO4, glucose (C6H 12 O6), add deionized water in a molar ratio of 1.03:0.2:0.2:1.01:0.05, stir thoroughly and transfer to a sand mill to grind to a slurry particle size of D 50 The particle size of the particles was 0.3 μm, and then spray drying was performed, with the air inlet temperature set at 200°C and the air outlet temperature set at 100°C to obtain a first mixture. The first mixture was placed in a nitrogen atmosphere and sintered at 500°C for 2 hours to obtain lithium manganese iron phosphate (referred to as LiMn 0.6 Fe 0.4 PO4 / C, indicating that carbon composite LiMn 0.6 Fe 0.4 PO4).
[0102] The lithium manganese iron phosphate, Co3O4, and LiH2PO4 obtained above were added to deionized water at a molar ratio of 1:0.05:0.15, and after being fully stirred, spray dried, and the air inlet temperature was set at 250°C and the air outlet temperature was set at 105°C to obtain a second mixture. The second mixture was placed in a nitrogen atmosphere and sintered at 700°C for 10 hours to obtain a positive electrode active material (referred to as 0.15LiCoPO4·LiMn 0.6 Fe 0.4 PO4 / C, indicating that LiMn composite with carbon materials 0.6 Fe 0.4 PO4 is the core and LiCoPO4 is the coating layer of the positive electrode active material, wherein the molar ratio of the core material to the coating layer material is 1:0.15), wherein the transition metal phosphoric acid is LiCoPO4, and the molar ratio of lithium manganese iron phosphate to the transition metal phosphate is 1:0.15.
[0103] Example 2
[0104] LiOH·H2O, Mn2O3, Fe3O4, (NH4)2HPO4, sucrose (C 12 H 22 O 11 ), add deionized water in a molar ratio of 1.05:0.35:0.1:1.02:0.03, stir thoroughly and transfer to a sand mill to grind to a slurry particle size of D 50 The particle size of the first mixture was 0.25 μm, and then spray drying was performed, with the air inlet temperature set at 220°C and the air outlet temperature set at 105°C to obtain a first mixture. The first mixture was placed in a nitrogen atmosphere and sintered at 450°C for 2 hours to obtain lithium manganese iron phosphate (referred to as LiMn 0.7 Fe 0.3 PO4 / C, indicating that carbon composite LiMn0.7 Fe 0.3 PO4).
[0105] The lithium manganese iron phosphate, V2O5, Ni2O3, and LiH2PO4 obtained above were added to deionized water in a molar ratio of 1:0.01:0.01:0.04, and after being fully stirred, spray dried, and the air inlet temperature was set to 260°C and the air outlet temperature was set to 110°C to obtain a second mixture. The second mixture was placed in a nitrogen atmosphere and sintered at 650°C for 10 hours to obtain a positive electrode active material (denoted as 0.04LiV 0.5 Ni 0.5 PO4·LiMn 0.7 Fe 0.3 PO4 / C, indicating that LiMn composite with carbon materials 0.7 Fe 0.3 PO4 as the core, LiV 0.5 Ni 0.5 PO4 is the positive electrode active material of the coating layer, wherein the molar ratio of the core material to the coating layer material is 1:0.04)).
[0106] Comparative Example 1
[0107] The lithium manganese iron phosphate core in Example 1 was directly used as the positive electrode active material.
[0108] The differences between the remaining embodiments and comparative examples and embodiment 1 are shown in Table 1-1, Table 1-2, and Table 1-3. In embodiment 11, Li2C2O4 is used as the second lithium source, and NaH2PO4 is used as the second phosphorus source.
[0109] Table 1-1
[0110]
[0111]
[0112] Table 1-2
[0113]
[0114] The positive electrode active materials in the above-mentioned embodiments and comparative examples were tested as follows, and the test results are shown in Table 2:
[0115] r, D value test: using Oxford Instruments Ultim Max 170mm 2The energy spectrum detector is used to cut the sample into sections, and the SEM scanning mode is adjusted to perform line scanning in the diameter direction. The energy spectrum detector receives characteristic X-rays of different elements, analyzes the selected line segment, and statistically presents the signal intensity change trend line of the specific element on the line segment. The diameter of the single sampling secondary ball scanning is D, and the length of the signal range of the specific element collected on one side is defined as r.
[0116] Particle size distribution test of primary particles: XRD Smartlab 9KW was used for testing, with a scanning range of 10°-80°, a voltage of 40kV, a current of 200mA, a step of 0.02°, and a scanning speed of 2° / min. The test results were obtained by using the WPPF grain size distribution function of SmartLabStudio II software to perform statistical calculations of the crystallite size according to the Fundamental Parameter method (FP method).
[0117] The molar ratio of lithium manganese iron phosphate to transition metal phosphate is calculated based on the molar ratio of lithium manganese iron phosphate to Me source.
[0118] Table 2
[0119]
[0120] The positive electrode active materials in the aforementioned embodiments and comparative examples were tested as follows. The test results are shown in Table 3.
[0121] Manganese dissolution test: accurately weigh 1.00±0.01g of lithium manganese iron phosphate sample into a 150mL beaker, then use a measuring cylinder to measure 100mL of 0.01mol / L hydrochloric acid, seal the beaker with a PE film, place it on a digital magnetic stirrer, adjust to 850rmp / min, stir for 30min and then remove it, place it in an ultrasonic device for 2min, place the ultrasonically treated sample in a 25℃±0.1℃ constant temperature water bath, and take it out after 2h. Place the sample solution on a filtration device, and after all the filtrate is completely filtered (filter membrane specification: 0.1um), wash the beaker with 10mL of water and pour the washing liquid into the filtration bottle to continue filtration, then add about 2mL of concentrated nitric acid, dilute all the filtrate into a 200mL volumetric flask, and take the sample after dilution for ICP-Mn element content (ppm) test.
[0122] Powder impedance test: Use the FT-301B series powder resistivity tester, take 1g of sample, put it into the specified mold, start measuring under 0.2T pressure, and read the automatic powder impedance measurement value.
[0123] The positive electrode active materials in the above-mentioned embodiments and comparative examples are made into button batteries, specifically as follows:
[0124] Preparation of positive electrode sheets: The above-mentioned positive electrode active materials, acetylene black and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:5:5, coated on aluminum foil and dried, and stamped into positive electrode sheets with a diameter of 12 mm and a thickness of 120 μm using a pressure of 100 MPa. The positive electrode sheets are then placed in a vacuum drying oven and dried at 120°C for 12 hours.
[0125] Assembly of button cell: The negative electrode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm; the separator uses a polyethylene porous membrane with a thickness of 25 μm; the electrolyte uses a 1 mol / L LiPF6 solution, and the solvent is an equal volume mixture of ethylene carbonate (EC) and diethyl carbonate (DEC). The positive electrode plate, separator, negative electrode plate and electrolyte are assembled into a 2025 button cell in an argon glove box with a water content and an oxygen content of less than 5 ppm. At this time, the battery is an unactivated button cell. After standing for 2 hours, it is charged to a cut-off voltage of 4.35 V with a current density of 0.1C to the positive electrode, and then charged at a constant voltage for 30 minutes, and then discharged to a cut-off voltage of 2.5 V with the same current density; the same method is repeated once more, and the battery is now an activated button cell.
[0126] The activated button cell was subjected to the following cycle performance test, and the test results are shown in Table 3.
[0127] Cycle performance test: At 25°C, the activated battery is charged and discharged continuously for 80 cycles at a current density of 1C in the voltage range of 2.5V-4.35V, and the changes in the average discharge voltage and discharge capacity during the cycle are statistically analyzed.
[0128] Table 3
[0129]
[0130] pass Figure 3-Figure 5 By comparison, it can be seen that the positive electrode active material in the present application has a small voltage loss before and after the cycle, the voltage attenuation of the charge and discharge platform is not large, and it has good structural stability.
[0131] As can be seen from Table 3, the powder impedance of the positive electrode active material in the embodiment is less than that of the positive electrode active material in the comparative example, indicating that the powder impedance of the positive electrode active material in the present application is low, which is conducive to the performance of electrical performance. The manganese dissolution level of the positive electrode active material in the embodiment is lower than that of the positive electrode active material in the comparative example, indicating that the positive electrode active material in the present application can effectively inhibit the manganese dissolution phenomenon and improve the structural stability of the positive electrode active material. Among them, the thickness of the coating layer of the positive electrode active material in Comparative Example 2 is too thick, which has a strong inhibition on manganese dissolution, and the voltage difference and cycle performance are also relatively good in terms of numerical values. However, the excessive coating thickness in Comparative Example 2 causes the powder impedance of the positive electrode active material to be too large, the average voltage of the first discharge cycle of the battery is obviously too low, and the capacity that the battery can release is significantly reduced. Even if it has a relatively low voltage difference and a better capacity retention rate, the performance of the battery's electrical performance is still very poor.
[0132] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: include: a core, the core comprising lithium manganese iron phosphate; a coating layer, the coating layer covering at least a portion of the surface of the core, the coating layer comprising a transition metal phosphate, Wherein, the particle size of the positive electrode active material is D, the thickness of the coating layer is r, and 0<r / D≤0.
2.
2. The positive electrode active material according to claim 1, characterized in that 0.1μm≤r≤5.0μm, and / or, 4μm≤D≤25μm.
3. The positive electrode active material according to claim 1, characterized in that In the positive electrode active material, the molar ratio of the lithium manganese iron phosphate to the transition metal phosphate is 1:(0.01-0.5).
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The distribution function k of the positive electrode active material is 0.7-1.3, wherein k=(D 90 -D 50 ) / (D 50 -D 10 ), D 90 D is the particle size corresponding to the cumulative volume particle size of primary particles in the positive electrode active material reaching 90%, 50 D is the particle size corresponding to the cumulative volume particle size of primary particles in the positive electrode active material reaching 50%, 10 It is the particle size corresponding to when the cumulative volume particle size of primary particles in the positive electrode active material reaches 10%.
5. The positive electrode active material according to claim 4, characterized in that 200nm≤D 90 ≤250nm,100nm≤D 50 ≤160nm,50nm≤D 10 ≤80nm。 6. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The lithium manganese iron phosphate satisfies the general formula Li a1 Mn x Fe 1-x M z P b1 O c1 , wherein M includes at least one of Mg, Si, V, Co, Ni, Ga, Zr, Mo, Sn, Nb, In, Ce, and W, 1<a1≤1.2, 0.5≤x<1, 0≤z≤0.2, 1≤b1≤1.2, and 4≤c1≤4.
2.
7. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The transition metal phosphate satisfies the general formula Li a2 Me y P b2 O c2 , wherein Me includes at least one of Cr, V, Ni, Co, Nb, Mo, Zr, Hf, W, Y, La, and Ce, 1<a2≤1.1, 1≤y≤1.1, 1≤b2≤1.1, and 4≤c2≤4.
2.
8. A method for preparing the positive electrode active material according to any one of claims 1 to 7, characterized in that: include: Mixing a first lithium source, a manganese source, an iron source, and a first phosphorus source to obtain a first mixture; performing a first sintering process on the first mixture to obtain lithium manganese iron phosphate; Mixing the lithium manganese iron phosphate, a second lithium source, a second phosphorus source, and a Me source to obtain a second mixture, wherein the molar ratio of the lithium manganese iron phosphate to the Me source is 1:(0.01-0.2); The second mixture is subjected to a second sintering treatment to form a transition metal phosphate on the surface of the lithium manganese iron phosphate to obtain the positive electrode active material.
9. The method according to claim 8, characterized in that The first lithium source and the second lithium source independently include at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium chloride; and / or, The first phosphorus source and the second phosphorus source independently include at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and sodium dihydrogen phosphate; and / or, The manganese source includes at least one of manganese tetraoxide, manganese dioxide, manganese carbonate, manganese oxalate, manganese chloride, manganese sulfate and manganese nitrate; and / or, The iron source includes at least one of ferrous oxalate, ferrous oxalate, ferrous acetate, ferrous acetate, ferrous nitrate, ferric nitrate, ferric phosphate, ferric oxide, ferrous sulfate, ferric sulfate, ferrous chloride and ferric chloride; and / or, The Me source includes at least one of metal oxides, hydroxides, phosphides, acetates and oxalates corresponding to the Me element.
10. The method according to claim 8, characterized in that The first mixture further includes a carbon source, and the carbon source includes at least one of citric acid, glucose, sucrose, soluble starch, salicylic acid, tartaric acid, oxalic acid, polyethylene glycol, and polyaniline.
11. The method according to claim 10, characterized in that The molar ratio of the first lithium source, the manganese source, the iron source, the first phosphorus source, and the carbon source is (1-1.5):(0-1):(0-1):(1-1.5):(0-0.1).
12. The method according to any one of claims 8 to 11, characterized in that: The temperature of the first sintering treatment is 350°C-650°C, and the time of the first sintering treatment is 2h-10h; and / or the temperature of the second sintering treatment is 550°C-850°C, and the time of the second sintering treatment is 6h-16h.
13. A battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode active material according to any one of claims 1 to 7, or the positive electrode active material prepared by the method according to any one of claims 8 to 12.
Citation Information
Patent Citations
Lithium manganese iron phosphate material and preparation method thereof, positive pole piece and lithium ion battery
CN117525331A
Composite phosphate positive electrode material and preparation method thereof
CN118877860A
Lithium manganese iron phosphate positive electrode material, and preparation method therefor and use thereof
WO2024244309A1
Cited By
Secondary battery, preparation method of positive electrode active material and electric device
CN121938885A